THE RELATIONSHIP BETWEEN TIBIAL TORSION AND PATELLOFEMORAL INSTABILITY (Fiep Bulletin - online, 2014)
Around 50% of injuries have the knee involved. The most common one is patellofemoral disfunction. Patellofemoral instability is manifested by subluxations or luxations. Foot effort influences on knee operation and structures. Tibial rotation can be both consequence of injuries and anatomic alteration and/or lower limb biomechanics, and patellofemoral instability might be due to ill-alignment of structures and biomechanic alteration or anatomic deformities. Therefore, the study aim has been to investigate the relation between tibial alteration in individuals with such disfunction. Twenty pacients had been evaluated with diagnosis of patellofemoral instability, without any injury associated. Discarded were the obese through CMI calculation. Evaluation consisted of questions and physical examination. Concerning, physical examination, presence of the real and apparent discrepancy of lower limbs, angle Q and of tibial torsion alteration, in addition to apprehension test. The sample is consisted of young adults, with predomination the female gender. Most of the pacients presented bilateral patellofemoral instability. Half of the individuals had luxated the patella. The Q angles and of tibia torsion were altered in a great part of the sample. From the results, it is concluded that there is relationship with tibial position in pacients with patellofemoral instability.
Keywords: patellofemoral articulation; patellofemoral instability; rotation tibial